Effects of monensin sodium and Xylanase on broiler growth performance - Owings, Bailey M.; Delfelder, C.J.; Beyer, R. Scott; Stark, Charles R.; Evans, C.E.; Yoder, Ashton D.; Jones, Cassandra K. (My University, 2017)
Due to recent trends in society there has been increasing consumer pressure on lowering the amount of antimicrobial used in poultry feed; however, antimicrobials have been used to improve nutrient digestibility in poultry diets for years. One potential alternative to replace antimicrobials is exogenous xylanase, an enzyme that is known to improve nutrient digestibility in higher fiber diets. However, its ability to replace an antimicrobial, such as monensin sodium, is unknown. Thus, the objective of this experiment was to improve nutrient digestibility by replacing monensin sodium with xylanase, and if this impact differs based on the fiber level of the diet. A total of 216 Cobb 1-d-old chicks (6 birds/cage and 6 cages/treatment) were fed 1 to 6 dietary treatments consisting of a corn- or wheat-based diet supplemented with either 0.10 g/kg monensin sodium (Coban 90; Elanco Animal Health, Greenfield, IN) or 16,000 betaxlylanase unit/kg beta 1-4, endoxylanase enzyme (Econase XT; AB Vista, Marlborough, UK. Specifically, treatments were: 1) corn-based with no monensin sodium or xylanase; 2) wheat-based without monensin sodium or xylanase; 3) corn-based with monensin sodium but no xylanase; 4) wheat-based with monensin sodium but no xylanase; 5) corn-based with xylanase but not monensin sodium; and 6) wheat-based with xylanase but no monensin sodium. Birds were fed ad libitum in battery cages for 21 days, while BW and feed intake were recorded weekly to determine BW gain, total feed intake, and FCR. Data were analyzed using the GLIMMIX procedure of SAS with cage as the experimental unit and treatment as the fixed effect. Treatment impacted (P< 0.01) Final BW, feed intake, and FCR. The corn-based control diet had improved (P< 0.05) FCR compared to the wheat-based control diet. In corn-based diets, neither the monensin sodium nor the xylanase improved (P> 0.05) FCR compared to the corn-based control. In wheat-based diets, xylanase (P< 0.05), but not monensin sodium (P> 0.05) improved FCR compared to the wheat-based control. In conclusion, this research suggests the xylanase improves carbohydrate digestibility in wheat-based diets, restoring FCR to that of corn-based diets. However, there was limited impact of feeding an antimicrobial in this setting.
Keywords: Spring 2017